Dating fluvial erosion: fluvial response to climate change in the Moselle catchment (France, Germany) since the Late Saalian. (19th December 2013) - Cordier, Stéphane; Frechen, Manfred; Harmand, Dominique
<x xml:space="preserve">Abstract</x> This paper focuses upon the youngest terraces of the Moselle and its tributary the Meurthe (NE France and SW Germany). It includes research on several sections, in particular the key sections of Golbey‐Pré Droué and Thörnich‐Hochrech (located in the vicinity of the Vosges Massif and in the Rhenish Massif, respectively), and the use of the Optically Stimulated Luminescence (OSL) dating method. Our investigations made it possible to obtain a more robust chronostratigraphical framework and to update the previous model of fluvial response to climate change. The results demonstrate that the Moselle terrace M3 (first terrace formed after the capture of the Upper Moselle by the Palaeo‐Meurthe) has the same age from the Vosges to the Rhenish Massif. The formation of this terrace included two main periods of sedimentation attributed to the Late Saalian (MIS 6) and the Early Weichselian (MIS 5), respectively. They were separated by a major episode of fluvial erosion that may be allocated to the MIS 6–5 transition on the basis of chronological and sedimentological evidence. This erosion led to the removal of most of the MIS 6 deposits, whereas the MIS 5 deposits have been widely preserved following the subsequent (MIS 5–4) terrace incision. This evolution somewhat contrasts with that observed in the Sarre valley, the main tributary of the Moselle, and with many fluvial systems in western Europe, which show better preservation of deposits from cold periods. This atypical behaviour is explained by the relationship between the fluvial evolution and the glaciers covering the upper Moselle catchment (Vosges Massif) during the Pleistocene cold periods.